2020
DOI: 10.1097/dbp.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

Onset, Trajectory, and Pattern of Feeding Difficulties in Toddlers Later Diagnosed with Autism

Abstract: Objective: To examine the emergence and trajectory of feeding difficulties in young children who are later diagnosed with autism spectrum disorder (ASD). Method: The Behavioral Pediatrics Feeding Assessment Scale (BPFAS) was administered to a sample of 93 toddlers with an older sibling with ASD-the high-risk group-and 62 toddlers with no known familial ASD-the low-risk group-as part of a larger infant sibling study. The BPFAS was completed by parents at 15, 18, 24, and 36 months of age. At 36 months, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…Consistent with previous studies [Palomo, Belinchón, & Ozonoff, 2006], our analyses identified several specific behaviors, such as “response to the child's name being called (18 months)” and “use of gestures (12 months),” as being more commonly delayed in the ASD group. Also consistent with previous prospective studies [Ashley, Steinfeld, Young, & Ozonoff, 2020; Landa, Stuart, Gross, & Faherty, 2013], differences in milestone attainment between the ASD and non‐ASD NDD groups were not apparent prior to 12 months. This would likely reflect the current challenge we face in capturing the very early course of ASD, as well as heterogeneity in onset patterns (i.e., some children may not exhibit clear deviations from typical development during the first year of their life, while others do).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous studies [Palomo, Belinchón, & Ozonoff, 2006], our analyses identified several specific behaviors, such as “response to the child's name being called (18 months)” and “use of gestures (12 months),” as being more commonly delayed in the ASD group. Also consistent with previous prospective studies [Ashley, Steinfeld, Young, & Ozonoff, 2020; Landa, Stuart, Gross, & Faherty, 2013], differences in milestone attainment between the ASD and non‐ASD NDD groups were not apparent prior to 12 months. This would likely reflect the current challenge we face in capturing the very early course of ASD, as well as heterogeneity in onset patterns (i.e., some children may not exhibit clear deviations from typical development during the first year of their life, while others do).…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence that feeding problems in ASD are of multifactorial origin, and they appear to be associated with the core behavioral characteristics of ASD. They reflect repetitiveness and preference for sameness, ritualism, unusual interest in sensory properties of food, but also diminished responsiveness to social reward, and increased reactivity in response to frustration [ 17 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, food selectivity and feeding disorders are present in neurotypical children, but they are more severe in ASD [ 44 ]. A study revealed that in ASD, the “picky eating” appears at early age and escalates more quickly than in typically developing children [ 43 ]. The food aversion does not resolve over time as the child develops, therefore it is not recommended to wait for the difficulties to disappear or that the child will “grow out of the problem” [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autism spectrum disorders (ASD) is a behaviorally defined complex neurodevelopmental syndrome characterized by impairments in social communication and restricted and repetitive behaviors, interests and activities, as well as abnormalities in sensory reactivity (American Psychiatric Association, 2013) that are frequently associated with different comorbidities such as disruptive behavior, gastrointestinal symptoms, and eating problems (Peverill et al, 2019). These atypical eating patterns are often governed by food rejection/denial or a preference for certain kinds of food (Bandini et al, 2017; Wentz, Björk, & Dahlgren, 2019), and may lie in a sensory‐associated physiological alterations probably caused by their behavioral problems (Ashley, Steinfeld, Young, & Ozonoff, 2020; Peverill et al, 2019).…”
Section: Introductionmentioning
confidence: 99%